2020
DOI: 10.3847/2041-8213/ab7306
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Spectral Shape Variation in Changing-look Seyfert Galaxy SDSS J155258+273728

Abstract: We analyze the X-ray, optical, and mid-infrared data of a "changing-look" Seyfert galaxy SDSS J155258+273728 at z;0.086. Over a period of one decade (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018), its broad Hα line intensity increased by a factor of ∼4. Meanwhile, the X-ray emission in 2014 as observed by Chandra was about five times brighter than that in 2010 by Suzaku, and the corresponding emissions in the V-band, mid-infrared W1 band brighten by ∼0.18, 0.32 mag, respectively. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 88 publications
1
27
0
Order By: Relevance
“…A change of R tr may generate a transition in the accretion regime. Ai et al (2020) find the similarity in the X-ray spectral evolution between CL-AGNs and black hole X-ray binaries, which implies that the observed CL-AGN phenomena may be related to the state transition in accretion physics. The hard X-ray emission from NGC 3516 (e.g., Ilić et al 2020) −0.12 on 2009 October 28 (Noda et al 2016).…”
Section: Discussionmentioning
confidence: 67%
“…A change of R tr may generate a transition in the accretion regime. Ai et al (2020) find the similarity in the X-ray spectral evolution between CL-AGNs and black hole X-ray binaries, which implies that the observed CL-AGN phenomena may be related to the state transition in accretion physics. The hard X-ray emission from NGC 3516 (e.g., Ilić et al 2020) −0.12 on 2009 October 28 (Noda et al 2016).…”
Section: Discussionmentioning
confidence: 67%
“…The appearance of the blue bump implies an increase of accretion rate of the black hole, and consequently the BELs become stronger due to photoionization. The similarity in the X-ray spectral evolution between CL-AGNs and black hole X-ray binaries indicates that the observed CL-AGN phenomena may be related to the state transition in accretion physics (Ai et al 2020). The latest research shows that X-ray variability observed in CL-AGNs is produced by changes of accretion disk structure and accretion rate (Igarashi et al 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Inspired by changes in the accretion states of X-ray binaries, Noda & Done (2018) showed that evaporation of the inner part of the disk drives a change in accretion states into a drop, which causes the CL of Mrk 1018. This appears to be supported by the analogy of CL-AGNs to X-ray binaries (Ruan et al 2019;Ai et al 2020;Liu et al 2019). Cooling fronts driven by a sudden change in the magnetic torque at the innermost stable circular orbit (Ross et al 2018), or magnetic fields supporting a geometrically thick disk (Dexter & Begelman 2019), or the radiation pressure instability (Sniegowska et al 2020) lead to a changing state.…”
Section: Introductionmentioning
confidence: 85%